Perawatan Kompresor Udara Guna Menunjang Olah Gerak Kapal MV. CHARLOTTE - Rahman Raising (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study is to detail the main causative factors of reservoir water tank issues that lead to delays in operating the main engine. The data analysis method used is qualitative descriptive analysis. The results show that the reasons for the compressor malfunction during the maneuvering of the MV. Charlotte include broken piston rings, damaged compressor cylinder head gaskets, leaks in high and low-pressure valves, and compression leaks in the compressor. The solution involves shutting down the compressor, closing the intake/outlet valves, removing the connecting rod bolts, replacing the piston rings, conducting a running test, cleaning the cylinder head surface, applying liquid gasket, and ensuring no leakage after installation. It is important to check and ensure the cylinder head bolts are tightened according to the manufacturer's manual. Additionally, shutting down the compressor, opening the valves, and performing skimming or replacing damaged components are necessary. Energy savings can be achieved by improving the compressed air system, which can reduce operational and maintenance costs. Compressor efficiency can be enhanced by using automatic controls to regulate compressor operation as needed and maintaining the system's air pressure as low as possible to minimize leakage. The conclusion emphasizes that efforts to ensure the compressor functions properly during ship maneuvers include repairing or replacing compressor components when damage is identified. If repairs are not possible, component replacement must be carried out immediately without delay.